Changes in sleep–wake rhythms, subjective sleep quality and pain among patients undergoing total hip arthroplasty. Issue 6 (30th April 2014) - Myoji, Yuriko; Fujita, Kimie; Mawatari, Masaaki; Tabuchi, Yasuko
Abstract : We evaluated nocturnal sleep–wake rhythms and subjective sleep quality on the first postoperative night compared with the preoperative night in 34 patients who had total hip arthroplasty (mean age: 61.9 years; 82.4% female) under spinal anaesthesia. We also examined secondary factors related to sleep disturbances after surgery. Patients wore an accelerometer (actigraph) during the preoperative period and the first postoperative night to track sleep–wake rhythms. Secondary end‐points were postsurgical pain and low back pain. Sleep parameters were measured objectively by actigraphy, and subjective sleep quality was measured by the Oguri–Shirakawa–Azumi Sleep Inventory, Middle‐Aged and Aged Version and found to worsen significantly after surgery. Actigram data showed a reduction in actual sleep time from 353.7 ± 121.2 min preoperatively to 263.8 ± 104.4 min postoperatively. The data indicate that normalized continuous sleep time is important for patient healing and well‐being and that postoperative sleep disturbance is related to low back pain more than to postsurgical pain.